2005
DOI: 10.1196/annals.1333.094
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Specific Variation in Glycation of Proteins in Diabetes: Evidence for a Functional Role of Amadoriase Enzymes

Abstract: The Amadori product fructoselysine (FL), an intermediate in the formation of many advanced glycation end products, may be deglycated by various pathways. These include spontaneous chemical degradation or enzymatic deglycation by amadoriases. This study was designed to compare changes in FL in various tissues in response to changes in glycemia, thereby testing tissue-specific deglycation. FL content in skin collagen, red cell hemoglobin, and total muscle, liver, and brain protein was analyzed by isotope dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In other words, CML may be involved in the development of age-related deterioration of skeletal muscle function. Generally, muscle shows the least glycation of several tissues, with the basal level of glycation in muscle protein of 0.2 mmol/mol lysine (Brown et al, 2005).…”
Section: Glycation and Aging Skeletal Musclementioning
confidence: 99%
“…In other words, CML may be involved in the development of age-related deterioration of skeletal muscle function. Generally, muscle shows the least glycation of several tissues, with the basal level of glycation in muscle protein of 0.2 mmol/mol lysine (Brown et al, 2005).…”
Section: Glycation and Aging Skeletal Musclementioning
confidence: 99%
“…2E) and m/z 686.39 (Fig. 2F) indicated that CEAM5 165-173 or 521-529 peptide was dominantly detected in one lung cancer serum, which was labeled with iTRAQ-121.These data implicated that the relative abundance of eight reporter ions was not affected by the use of elution buffer containing H 2 18 O, and the IGEL method could have a great potential for the reliable identification of glycosylation sites on even small quantity of proteins, such as serum CEA (ng/mL range). Moreover, the use of 8-plex iTRAQ tags enabled the relative quantification of glycan structures on each glycosylation site.…”
Section: Isotopic Glycosidase Elution and Labeling On Lectin-column Cmentioning
confidence: 58%
“…2C and 2D). The peak of m/z 685.40 corresponding to the CEAM5 peptide with 16 O-incorporated asparagine residue was hardly detectable in Figure 2C, indicating that H 2 16 O contamination in PNGase F reaction with H 2 18 O could be almost negligible for the mass spectrometric analysis. Additionally, the MS/MS spectrum acquired from the precursor ion m/z 686.39 clearly showed the 3-Da increase of the asparagine residue (Fig.…”
Section: Isotopic Glycosidase Elution and Labeling On Lectin-column Cmentioning
confidence: 97%
See 1 more Smart Citation
“…Experimental data suggest that tissues vary in their susceptibility to different AGEs: certain tissues may be more sensitive to AGE-induced DNA damage or possess weaker defense mechanisms. The tissuespecific variation in the glycation of proteins was demonstrated in healthy rats with the highest levels of fructoselysine in skin collagen, followed by hemoglobin, whereas the brain and liver reached approximately one third of the skin collagen content [83] . In diabetic rats the fructoselysine content of the skin and erythrocytes was enhanced 4-to 5-fold, and that of muscle 3-fold compared to controls, while the liver showed only a slight increase and no difference was observed in the brain [83] .…”
Section: Open Questions On the Putative Role Of Ages In Cancer Develomentioning
confidence: 99%